Transition readiness in adolescents with juvenile idiopathic arthritis and their parents: Our single-center experience - Dragana Lazarević; Stefan Đorđević; Dušica Novaković; Maja Zečević; Gordana Sušić (Archives of Rheumatology, 2022)
Objectives: We aimed to identify characteristics of juvenile idiopathic arthritis (JIA) patients associated with good self-management skills in the transition readiness process and to investigate the readiness of JIA patients and their families for the transition into the adult healthcare system. Patients and methods: Between March 2021 and June 2021, a total of 44 JIA patients (9 males, 35 females; median age: 15.1 years; range, 12.3 to 19.3 years) admitted to the pediatric rheumatology outpatient and inpatient clinics and their parents were included. Transition Readiness Assessment Questionnaire (TRAQ) was cross-culturally adapted. The TRAQ was administered to all JIA patients and their parents at one point. Demographic and clinical data were collected. Results: Fourteen (31.8%) of 44 JIA patients had a concomitant disease, while 10 (22.7%) of them had uveitis. Eleven (25%) of them had a family history of autoimmune diseases. In total, 21 (47.7%) of JIA patients were receiving biologics. There was a strong correlation between older age and total TRAQ scores among patients (ρ=0.799, p<0.001) and a moderate correlation between older patient age and total TRAQ scores among parents (ρ=0.522, p<0.001). Patient and parent total TRAQ scores were strongly correlated (ρ=0.653, p<0.001). There was no significant association of JIA patient characteristics (JIA disease subtypes, disease duration, gender, concomitant diseases, uveitis, family history of autoimmune diseases, number of hospitalizations, and treatment with biologics) with TRAQ scores and JIA patients’ and parents’ readiness for transition. Conclusion: Transition readiness of JIA patients increases with advancing age. There is no significant difference between transition readiness for JIA patients and their parents.